Nutritional Support in Critically Ill Patients - Selfie Selfie; Marcellus Simadibrata (The Indonesian Society for Digestive Endoscopy, 2018)
Critically ill patient is at risk of malnutrition. The aim of nutritional support is to prevent malnutrition and its complication, and also fulfill macro- and micronutrient, reduce nitrogen deficit, and improve inflammaroty response. In critica patient with stable hemodynamic, enteral nutrition should be started early at 24-48 hours while patient not in ebb/resuscitation phase. Parenteral nutrition is not recommended in the first 24 hours of ICU care if enteral feeding is feasible. Parenteral nutrition is considered after 5-7 days, except poor enteral condition. Delay of parenteral nutrition for 7 days reduce risk of infection, increase recovery time, and reduce cost. On the first day, calorie should reach one third of actual need, increased to half to two third on second day, and full calorie on the third day. Total calorie need is 25-35 kcal/ideal bodyweight. Source of calorie is 60-70% carbohydrate and 30-40% lipid. Daily fluid need is 30-40 mL/kgBW/day or 1.0 – 1.5 mL/kcal calorie intake. Several important micronutrients to fulfill is sodium, potassium, calcium, phosphate, and magnesium. Three main consideration of nutritional support is route, type of formula, and when to start nutritional support.